MEKANISME PENYUSUNAN ANGGARAN PADA DINAS KOPERASI USAHA KECIL MENENGAH DAN PERDAGANGAN KABUPATEN PURWOREJO - Handayani, Melina (Prospect : Jurnal Manajemen dan Akuntansi, 2023)
The Reformation Era demands the implementation of regional autonomy, authority in the field of regional finance which includes collection of sources of regional income, administration, management, accountability, supervision of regional finances and of course the determination of the Regional Revenue and Expenditure Budget (APBD) becomes the authority of the region. The amount of the budget in a regional apparatus organization depends on the amount of the APBD of a region, the budget planning process is very important related to the implementation of programs and activities in public organizations or regional apparatus organizations as well as at the Dinas Koperasi Usaha Kecil Menegah dan Perdagangan.The budget preparation process is carried out by referring to the budgeting mechanism so that the implementation of programs and activities can run optimally. The analysis uses interactive analysis model data techniques from three main componen, data reduction, data presentation and data verifictation. Presentation of data either trought referrals or interviews with resource person from the planning sector at the office uses presentation that will clarify the research.Keyword: financial planing, bugeting mechanism